Analysis of Student Responses to Student Worksheets Based on Project Based Learning Models - Yusnidar, Yusnidar; Epinur, Epinur; Nadila, Nila A’yun (Integrated Science Education Journal, 2023)
Purpose of the study: This research aims to determine student responses to project-based learning in chemistry courses. Methodology: This research used mixed methods with a sequential explanatory design. The samples involved in this research were 90 students from the chemistry study program. The sampling technique is purposive sampling. The instrument used to collect quantitative data was a questionnaire sheet distributed to students to measure responses, while the instrument to collect qualitative data was interviews conducted with chemistry students. Data analysis was carried out to process quantitative data based on descriptive statistics, and qualitative data was analyzed based on Miles and Huberman's theory and supported by documentation studies. Main Findings: The results obtained from this research are that chemistry students' responses to project-based learning are classified as good. The importance of the Project Based Learning Model (PjBL) lies in its ability to inspire active involvement in solving real problems, thus facilitating the development of critical and analytical thinking skills. Novelty/Originality of this study: The latest research is that the research sample involved was from the chemistry education study program to measure the response to project-based learning. This research is limited by only measuring responses, so researchers do not know the truth of the project-based learning process. So, recommendations that can be given in further research are to directly implement the project-based learning process to strengthen the questionnaire results in this research.